The drag effects of energy-water constraints on China’s economic growth under carbon mitigation goals - Yu, Xinxin; Chen, Yifan; Jiang, Mingdong; Zhong, Guanyu; Xu, Heyichen; Shen, Xiaomei; Kong, Qianhui (Frontiers in Earth Science, 2023)
Energy and water resources function as the base for humans’ socioeconomic development, which are closely linked with each other in the production process. With the rapid economic development, the contradiction between the supply and demand of energy and water resources has become acute. Meanwhile, the carbon reduction goals further enhanced the energy consumption constraints. Water, another necessary resource in energy production, whose recycling process generates many carbon emissions is also expected to be limited under carbon reduction goals. Furthermore, the constraints of these two basic factors will inevitably have a significant impact on economic growth. Therefore, exploring the effect of energy and water constricts on the economic growth under climate goals is essential for policy maker to minimize the economic loss during carbon control. To realize this aim, we constructed a drag effect model of energy-water resources on economic growth. Then the spatial-temporal characteristics of the energy-water drag effects on China’s economic growth have been further analyzed. In addition, the interference with the economic drag effects of energy and water resource exerted by dual carbon goals has been discussed. We find that China’s economic growth rate was reduced by 7.72% and 7.99% due to energy and water resources constraints respectively. In terms of the temporal trend, the fluctuation of the energy-water growth drag effect was mostly positive, and the growth drag of energy on economic growth is slightly greater than that of water resources. As to spatial distribution, the constraint effects of energy and water resources on economic growth showed a distribution pattern of “double high” in the East and “double low” in North China. According to the simulation results, China’s energy-water drag effect on the economic growth is relatively higher under the baseline and strong carbon control scenarios, than that under the weak carbon control decrease. In this view, if energy constraints are enhanced under strong carbon control scenarios, the carbon mitigation might be accompanied by more economic loss. Based on this, this paper discusses the synergy and heterogeneity of energy-water constraints and proposes a constraint mitigation path for achieving a win-win situation of economic development and dual-carbon goals.